The Economic Impact of East-West Migration on the European Union - Martin Kahanec; Mariola Pytliková (Global Labor Organization (GLO), 2017)
This study contributes to the literature on destination-country consequences of international migration with investigations on the effects of immigration from new EU member states and Eastern Partnership countries on the economies of old EU member states over the years 1995-2010. Using a rich international migration dataset and an empirical model accounting for the endogeneity of migration flows we find positive and significant effects of post-enlargement migration flows from new EU member states on old member states' GDP, GDP per capita, and employment rate and a negative effect on output per worker. We also find small, but statistically significant negative effects of migration from Eastern Partnership countries on receiving countries' GDP, GDP per capita, employment rate, and capital stock, but a positive significant effect on capital-to-labor ratio. These results mark an economic success of the EU enlargements and EU's free movement of workers.
Keywords: J15; J61; J68; 330; EU enlargement; free mobility of workers; migration impacts; European Single Market; east-west migration; Eastern Partnership